Fused deposition modelling process: a literature review - Blaj, M; Oancea, G (IOP conference series. Materials Science and Engineering, 2021)
It is well-known that the Additive Manufacturing is a one of the key technology of the fourth industrial revolution, and Fused Deposition Modelling process is one of the most used processes with a large applicability in many domains. Based on a literature review, the paper aims to approach the topic of the main process parameters definitions which ensure the management over the printing process. The paper is also focused on the current optimized manufacturing process, presenting the latest approach from the design phase to the post processing step. Another subject is referring to the used materials, with an accent over the composite carbon filaments in the context of Fused Deposition Modelling process limitations. In order to sum up, based on the main directions and purposes of the further research, this paper aims to be a binder between the current knowledge and what will be studied regarding Fused Deposition Modelling process.